2022
DOI: 10.1200/jco.2022.40.4_suppl.250
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness and safety of camrelizumab-based neoadjuvant therapy in resectable esophageal cancer: Initial results of a prospective multicenter observational study.

Abstract: 250 Background: Camrelizumab, a fully humanized monoclonal anti-PD-1 antibody, has shown promising efficacy with good tolerance in neoadjuvant therapy of resectable locally advanced esophageal cancer (EC). The present study aimed to investigate the effectiveness and safety of camrelizumab-based neoadjuvant therapy in a comparatively larger number of resectable EC patients in a real-world setting and initial results were reported here. Methods: In this prospective multicenter observational study (ChiCTR2000039… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although the number of participating patients is limited, preoperative combination therapies have shown ideal pathological complete response (PCR) rate, ranging 21.2%-40.0%, with an acceptable safety profile. Effect of neoadjuvant camrelizumab-containing regimens have also been studied in a multicenter observational study[ 21 ], which showed a complete resection and PCR rate of 86.4% and 21.3%, respectively, among 255 patients with ESCC. Although the survival benefit for patients after neoadjuvant combination ICI + chemotherapy remain unknown, follow-up data was reported in several trials.…”
Section: Current Evidence Of Icis For Esccmentioning
confidence: 99%
“…Although the number of participating patients is limited, preoperative combination therapies have shown ideal pathological complete response (PCR) rate, ranging 21.2%-40.0%, with an acceptable safety profile. Effect of neoadjuvant camrelizumab-containing regimens have also been studied in a multicenter observational study[ 21 ], which showed a complete resection and PCR rate of 86.4% and 21.3%, respectively, among 255 patients with ESCC. Although the survival benefit for patients after neoadjuvant combination ICI + chemotherapy remain unknown, follow-up data was reported in several trials.…”
Section: Current Evidence Of Icis For Esccmentioning
confidence: 99%